Blepharospasm: A genetic screening study in 132 patients. (July 2019) - Hammer, Monia; Abravanel, Alexandra; Peckham, Elizabeth; Mahloogi, Ava; Majounie, Elisa; Hallett, Mark; Singleton, Andrew
Abstract: Introduction: Blepharospasm is a common type of focal dystonia that involves involuntary eyelid spasms and eye closure. In familial cases, an autosomal dominant pattern of inheritance is noted with reduced penetrance. Few genes have been associated with the disease including GNAL and CIZ1 . A whole exome sequencing study published lately suggested TOR2A and REEP4 as potential candidate genes. Methods: Sanger sequencing of GNAL, CIZ1, TOR2A and REEP4 exons including exon-intron boundaries in 132 patients diagnosed primarily with blepharospasm and/or Meige's syndrome. Results: All variants detected in GNAL, CIZ1 and TOR2A seem to be benign. Sequencing of REEP4 revealed the presence of two nonsynonymous SNVs, one potential splice site variant and one indel all predicted to be damaging by in silico algorithms. Conclusion: Sequencing REEP4 in larger blepharospasm cohorts and functional studies will need to be performed to further elucidate the association between REEP4 and the disease. Highlights: Sanger sequencing of REEP4 reveals likely pathogenic variants in patients with blepharospasm. REEP4 is a good candidate gene for blepharospasm. Further studies are needed to elucidate the association between REEP4 and blepharospasm.